The religious world in late Ming China as seen through the 勵修一鑬 Lixiu yijian: how was Christianity integrated into the local society of Fujian? - Yang, V (2018)
Past studies on expeditions by missionaries to Ming China have mainly focused on the doctrinal transmission of Christianity and examined how Chinese elite received and interpreted the Christian ideas. However, the aim of this paper is to shift the focus to the local sphere in order to explore how Christianity was “done” on the local level. In this respect, this study takes two arguments as a point of entry – both pioneering but very different in perspective. On the one hand, the French sinologist Jacques Gernet proposed a theory of “cultural incommunicability”, in that differences in philosophical framework and cultural history prevented local Chinese people from grasping the essence of the doctrine. As a consequence, Christianity “failed” to be transmitted to China.1 On the other hand, Erik Zürcher has asserted that Christianity integrated into the local community by becoming accommodated by both missionaries and local people, and localised to the pre-existing religious and social world. Following Zürcher’s argument, scholars such as Nicolas Standaert, Adrian Dudink, Eugenio Menegon, and Henrietta Harrison have produced important scholarship examining the different dimensions of local Christianity from Ming China onwards. In this paper, I will follow Zürcher’s argument of localisation and further discuss how Christianity integrated and transformed into a local religious practice, through looking at stories in the Lixiu yijian 勵修一鑬. In dealing with the notion of “religion”, I will be using Barend J. ter Haar and Adam Chau’s conception of religion as something that people “do” and “practise”. Chau has proposed “to look at the Chinese religious landscape through the lenses of ‘modalities of doing religion’ and ‘ritual polytropy’.” In brief, he argues that religions in China should not be studied as coherent conceptual aggregates, such as “Buddhism” or “Daoism”. Rather, we should look at how people “do” religion on the ground. Chau observes that China was characterised by ritual-based and polytrophic religiosity—people made use of different coexisting and competing ritual providers and liturgical programmes in order to acquire efficacious ritual services.2 In his studies on the Non- Action Sect, ter Haar argues that the sect initially emerged from a group reflection on the practices. Nevertheless, through closer analysis, he demonstrates that for people of the sect, the reading and reciting of the scriptures was the core religious activity. The religious experience was achieved not through a mere reflection on the texts, but, as the title of his book Practicing Scriptures suggests, through practice of the scriptures. [introduction continues in thesis]